USING DIAMETER VARIATION INDEX OF PIONEER SPECIES FOR CLASSIFICATION AND MODELING TROPICAL FOREST YIELD - Nascimento, Rodrigo Geroni Mendes; Machado, Sebastião do Amaral; Figueiredo Filho, Afonso; Higuchi, Niro (Biofix Scientific Journal, 2016)
This study sought to classify the productivity of a representative area of tropical forest, as well as to analyze the relationship between the structural variability of pioneer species and the yield of three management regimes. The study area is located at the Tropical Forestry Experimental Station belonging to INPA (National Institute for Amazon Research), approximately 90 km from downtown Manaus, in the State of Amazonas, Brazil. Data were collected from twelve 1 ha sample plots. Diameter was measured annually for all individuals with DBH 10 cm between the years 1990 and 2008. Pioneer species served as the basis for calculating the Diameter Variability Index VI% over time. Three classes of variability were established according to the guide curve technique used for site classification by the dominant height. Biological and probabilistic functions were used to model VI% as a function of time of exploitation, as well as the volumetric yield over time as a function of VI%. There is an inverse relationship between VI% and yield, which allows classification of site yield and conception of global yield models to which present good statistics of precision and adjustment, allowing the prediction of productivity and their dynamics throughout the time.